Behavioral health risk profiles of physical education undergraduates - Luciana Zaranza Monteiro; Andrea Ramirez Varela; Bruno Alves Lira; Priscila de Souza; Daniel Junior de Oliveira Gomes; Leonardo Chagas Contiero; José Maria Thiago Bonardi (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aims: To analyze the prevalence of risky behaviors among physical education undergraduates; to determine prevalence of risk factors for non-communicable chronic diseases (NCCD) among university, and; to determine the association between healthy life habits and physical activity. Method: A cross-sectional study with 903 undergraduate Physical Education students. The study used a self-administered questionnaire on health-related life habits. All questions were obtained from the Surveillance of Risk and Protection Factors for Chronic Diseases through Telephone Interviews. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (95% CI). Results: Of the 903 students, 57.4% were women, 67.6% were between 20-29 years of age, 68.7% consumed alcohol, 28.5% did not do physical activity, and 33.2% were overweight. Regarding the eating habits considered a risk for NCCD, women exhibited more risk factors than men, whereas 41.1% drank more full-fat milk (p = 0.01) and 31.8% ate more fatty meats, while men drank more soda (p < 0.01). Physically active students consumed more fruits (p < 0.01) and salads (p = 0.01) and drank less soda (p < 0.01). The physically inactive students had a high prevalence of getting diabetes (p < 0.01) and of suffering from hypertension (p = 0.01) and high cholesterol (p < 0.01). Conclusions: University students in our study had unhealthy lifestyles. There is an urgent need for both a formulation and implementation of public health policies to promote health and decrease risk factors for NCCD.